El justo despido y el mercado laboral: Una aplicación para España (2005)
This article analyzes, in the first place, the effect of legislation on dismissals in labor market. In a second place, it shows how the existence of a wider dismissal legislation such as the case in Spain, has not implied that the number of cases against workers have increased, because this result has greatly depended on the evolution of unemployment rate. In this way, the results show that 1% of strike rate increases in 14% the number of dismissals won by workers for the Spanish case.